Post-rationalist cognitive psychotherapy process: Experience in adolescents with emotional dysregulation - Cerda Aedo, Bárbara (2021)
Objective: To understand the experience of adolescents with emotional dysregulation in a postrationalistcognitive psychotherapy process. Methodology: Qualitative approach, adopting aphenomenological perspective. It seeks to generate a grounded theory through a comprehensivehypothesis from the post-rationalist cognitive theoretical model (Krause, 1995). Results: Significantchanges could be observed in the operated patients with respect to the main indicators of emotionaldysregulation that were made known during the first sessions, verbalized both by the patients andthe information obtained from the establishment from which they were derived. The adolescents wereable to experience emotions, at the level of understanding the sense of continuity they maintained andhow this is altered when they become an observer of themselves. Conclusions: It was possible toaccompany the adolescent in this process, experiencing and knowing the different aspects involved incarrying out a therapy, both professionally and personally.